Perceived Managerial Competence of First-Line Nurse Managers: A Comparative Analysis Among Public Hospitals. (August 2020) - Gunawan, Joko; Aungsuroch, Yupin; Fisher, Mary L.; McDaniel, Anna M.; Marzilli, Colleen
Knowing the perceptions of first-line nurse managers (FLNMs) regarding their managerial competence is an important step to resolve disparities between their perceived competence and the competencies required for them to effectively function in their roles. Yet, evidence examining managerial competence of FLNMs among public hospitals in Indonesia is sparse. To fill this gap, we conducted a cross-sectional study aimed to identify managerial competence of FLNMs according to hospital type and ownership. This study was conducted from January to May 2018 and included a convenience sample of 233 FLNMs selected from 13 public hospitals. We used the Indonesian-First-Line Nurse Managers Managerial Competence Scale (I-FLNMMCS) to measure managerial competence. Descriptive statistics, Kruskal–Wallis, and Dunn's Pairwise were used for data analysis. Findings showed a significant difference in managerial competence according to the hospital type ( p  < .05). The FLNMs with a Diploma III, those relatively older, in their position for 7 or more years, and with managerial training in Type A hospitals (larger hospitals) had the highest managerial competence. The FLNMs with a bachelor's degree, those relatively younger, with less training, and those in their position for 3 to 4 years in Type B and C hospitals (smaller hospitals) had less managerial competence. A significant difference was also found in managerial competence according to hospital ownership ( p <.05). Public hospitals owned by the Ministry of Health of Indonesia had the highest competence among the others. This study is useful for guiding future policy work for human resource development in public hospitals.